Pengaruh Lama Perendaman Basis Gigi Tiruan Resin Akrilik Polimerisasi Panas Dalam Larutan Kopi, Teh, dan Jamu Terhadap Stabilitas Warna - Sitompul, Rona Oktavia; Dahar, Eddy (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Heat-cured acrylic resin (HCAR) denture base is widely used in prosthodontic practice due to its affordability and ease of manipulation. However, its hydrophilic nature and porosity make it prone to discoloration when exposed to colored beverages. This study aims to evaluate the effect of immersion duration in coffee, tea, and herbal solutions on the color stability of HCAR denture base. Sixty cylindrical HCAR samples (20 mm × 3 mm) were immersed in each solution for 3, 5, and 7 days, and color changes were measured using a spectrophotometer. Data were analyzed using one-way ANOVA. The results showed no significant differences in color stability among the groups (p > 0.05). The highest mean discoloration was observed in the herbal group after 7 days (1.04 ± 0.10), while the lowest was in the coffee and tea groups after 3 days (0.85 ± 0.15 and 0.85 ± 0.17). Clinically, these findings are significant because they suggest that short-term exposure to commonly consumed beverages such as coffee, tea, and herbal drinks does not significantly affect the color stability of HCAR denture bases within an estimated 2.8-year usage period. This insight is valuable for prosthodontists when advising patients on dietary habits and maintenance routines to preserve the aesthetic quality of their prosthetic appliances over time.